Factors Affecting The Bajo Tribe Construction of Children’s Education In Sapeken Islands - Supianto Supianto (IKIP PGRI Bojonegoro, 2022)
Abstract: Equitable access for education can be a measure of a country's justice. Although almost all countries, including Indonesia, have echoed campaigns on education for all, this has not always been successful. Various obstacles were faced, such as socio-cultural constraints, especially for isolated tribes. This study aims to determine the factors that influence parents' construction in the Bajo Tribe towards children's education in the Sapeken Islands. This research is qualitative research with a phenomenological method. The study was conducted for one year with ten subjects. Data was obtained through participatory observation, then analyzed using the NVivo program. The results show that at least five factors influence the construct of Bajo parents on their children's education. The five factors include religious and moral values, relations with the outside world, availability of transportation facilities, educational facilities, and access to information. Abstrak: Pemerataan akses pendidikan dapat menjadi ukuran keadilan suatu negara. Meskipun hampir semua negara, termasuk Indonesia, telah menggemakan kampanye pendidikan untuk semua, namun hal ini tidak selalu berhasil. Berbagai kendala dihadapi, seperti kendala sosial budaya, terutama bagi suku terasing. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi pembinaan orang tua Suku Bajo terhadap pendidikan anak di Kepulauan Sapeken. Penelitian ini merupakan penelitian kualitatif dengan metode fenomenologis. Penelitian dilakukan selama satu tahun dengan sepuluh subjek. Data diperoleh melalui observasi partisipatif, kemudian dianalisis menggunakan program NVivo. Hasil penelitian menunjukkan bahwa setidaknya ada lima faktor yang mempengaruhi konstruk orang tua Bajo terhadap pendidikan anaknya. Kelima faktor tersebut antara lain nilai agama dan moral, hubungan dengan dunia luar, ketersediaan sarana transportasi, sarana pendidikan, dan akses informasi.